How the body remembers its skills: Memory and material engagement - Malafouris, L; Koukouti, M (Imprint Academic, 2018)
What are bodily memories made of? Where do body memories reside and what forms do they take? What is the relation ship between embodied memory and material culture? This paper adopts a material engagement approach and sets out to explore body memory as a skilful engagement with the material world. We examine the nature of body memory from a distributed, enactive, and transactional perspective. We use the examples of bicycle riding and pottery making to examine more closely what is changing in the way we understand bodily memory when we approach it from such a distributed and enactive anthropological perspective. Overall, we wish to make a case for the primacy of material engagement over body memory and to propose that the way a body remembers its skills is by re-enacting them inside the world using available forms of material culture and not by re-presenting them inside the brain.